The Pentagram as a Living Cross - Maria Urmă (Anastasis: Research in Medieval Culture and Art, 2016)
The pentagram is a symbol present in most of the world cultures. It is a symbol of the human being in action, a quintessence of the universal principles, but also a symbol of the evolution, of the becoming, of life after all. This symbol must be regarded in relationship with another fundamental symbol: the cross, but not a cross of the crucifixion, rather a cross of the Resurrection, as a fundamental structure of the universe. The use of pentagram in modern times must be interpreted under the aspect of its symbolic force, perpetuated in time. The possible interpretations must start from its fundamental meanings, defined in time.